2017
DOI: 10.1016/j.neuroimage.2016.10.048
|View full text |Cite
|
Sign up to set email alerts
|

The real-time fMRI neurofeedback based stratification of Default Network Regulation Neuroimaging data repository

Abstract: This data descriptor describes a repository of openly shared data from an experiment to assess inter-individual differences in default mode network (DMN) activity. This repository includes cross-sectional functional magnetic resonance imaging (fMRI) data from the Multi Source Interference Task, to assess DMN deactivation, the Moral Dilemma Task, to assess DMN activation, a resting state fMRI scan, and a DMN neurofeedback paradigm, to assess DMN modulation, along with accompanying behavioral and cognitive measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 74 publications
(106 reference statements)
2
27
0
Order By: Relevance
“…Therefore, in general, it can be said that with an increase in the SMR wave in the CZ area, some improvements in working memory will be seen. Also, one other part of the protocol used in this study was to suppress theta; in other words, our findings showed neurofeedback training had positive effects on individual's mental functioning and cognitive processing; this finding is congruent with findings of Hans and Mayer [41], Oh [42] and McDonald [43]. Moreover, neurofeedback therapy helped students to develop skills required for reading comprehension, while students treated by Fernald's multisensory approach showed better indicators of written expression; however a combination therapy that integrated both groups (Fernald and neurofeedback), could have significant effect on both variables mentioned above in each isolated group [10].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, in general, it can be said that with an increase in the SMR wave in the CZ area, some improvements in working memory will be seen. Also, one other part of the protocol used in this study was to suppress theta; in other words, our findings showed neurofeedback training had positive effects on individual's mental functioning and cognitive processing; this finding is congruent with findings of Hans and Mayer [41], Oh [42] and McDonald [43]. Moreover, neurofeedback therapy helped students to develop skills required for reading comprehension, while students treated by Fernald's multisensory approach showed better indicators of written expression; however a combination therapy that integrated both groups (Fernald and neurofeedback), could have significant effect on both variables mentioned above in each isolated group [10].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, in general, it can be said that with an increase in the SMR wave in the CZ area, some improvements in working memory will be seen. Also, one other part of the protocol used in this study was to suppress theta; in other words, our findings showed neurofeedback training had positive effects on individual's mental functioning and cognitive processing; this finding is congruent with findings of Hanslmayr [41], Oh [42] and McDonald [43]. Moreover, neurofeedback therapy helped students to develop skills required for reading comprehension, while students treated by Fernald's multisensory approach showed better indicators of written expression; however a combination therapy that integrated both groups (Fernald and neurofeedback), could have significant effect on both variables mentioned above in each isolated group [10].…”
Section: Discussionsupporting
confidence: 89%
“…Following our request, we received data from 24 independent neurofeedback studies with data from 261healthy participants [studies 1, 2, 4, 5, 7, 9-15, 18-21, 24] Table 1 provides an overview over all studies (Auer et al, 2015;Blefari et al, 2015;Emmert, Kopel, et al, 2017;Kim et al, 2015;Kirschner et al, 2018;Koush et al, 2015, Koush et al, 2013MacInnes et al, 2016;Marins et al, 2015;McDonald et al, 2017;Megumi et al, 2015;Papoutsi et al, 2020, Papoutsi et al, 2018Scharnowski et al, 2012Scharnowski et al, , 2015Skouras & Scharnowski, 2019;Sorger et al, 2018;Spetter et al, 2017;Yao et al, 2016;Young et al, 2017;Zich et al, 2020).…”
Section: Received Datamentioning
confidence: 99%